Versatile Routing and Services with BGP : Understanding and Implementing BGP in SR-OS. (Wiley, 2014)
Design a robust BGP control plane within a secure, scalable network for smoother services A robust Border Gateway Protocol setup is vital to ensuring reliable connectivity, an essential capability for any organization. The Internet has become a necessary, always-on service in homes and businesses, and BGP is the protocol that keeps communication flowing. But BGP also has become crucial to delivery of intra-domain business services. But the network is only as reliable as BGP, so service enablement depends upon making BGP more stable, reliable, and service-rich. Alcatel-Lucent Service Router Ope.